Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


(-a)(-b)=ab (positive=(negative)(negative))
(a)(b)=ab(positive =(positive)(positive))
(-a)(b)=-ab(negative=(positive)(negative) or vice versa)

generalization: like terms=positive
unlike terms=negative

rule. even no. of negative is equal to positive
. odd no. of negative is equal to negative
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts